Model Pembelajaran Kooperatif Make a Match : Pengaruhnya Terhadap Kemampuan Berhitung Anak - Veryawan Veryawan; Anita Yus; Yasaratodo Wau (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to determine the effect of using the make-a-match cooperative learning model on children's numeracy skills. This quasi-experimental research was conducted at Fadnur Aisyah Islamic Kindergarten, North Sumatra, Indonesia. Researchers took 30 students aged 5-6 years with a specific purpose as a sample. We were collecting data using observation sheets to assess children's numeracy skills. The research instruments include mentioning numbers, counting pictures, connecting with symbols, and adding simplicity. The data analysis technique used is the one-way ANOVA test. The results showed that the average numeracy ability of children using the make-a-match learning model was higher than the expository learning model. Therefore, the implications of the make-a-match cooperative learning model can support numeracy skills in early childhood